Analisis Resonansi dan Rasio Damping Menara Masjid Baiturrahman terhadap guncangan gempa bumi - Angelia M. Purba; Daniel H. S. Napitu; Meidi W. Lestari; Juanto Simangunsong; Elferida Hutajulu; Nicodemus F. Hutabarat; Aprima A. Matondang (Postgraduate, University of Mataram, 2026)
The electrification of urban public transportation has become a key strategy for reducing energy consumption and greenhouse gas emissions while improving overall system efficiency. This study develops a comprehensive modeling framework to evaluate the energy consumption and charging infrastructure requirements of electric bus fleets operating in urban environments, incorporating key operational parameters such as travel distance (126 km/day), vehicle energy efficiency (1.2–1.5 kWh/km), fleet size (5–30 buses), and regenerative braking efficiency (25%). The results indicate that a single electric bus consumes approximately 151.2 kWh/day under typical operating conditions, which can be reduced to 113.4 kWh/day through regenerative braking, representing a 25% improvement. At the fleet level, electricity demand increases proportionally, reaching 0.76 MWh/day (5 buses), 1.51 MWh/day (10 buses), 2.27 MWh/day (15 buses), and 3.02 MWh/day (20 buses). Furthermore, fast-charging systems with a capacity of 150 kW can deliver up to 300 kWh within 2 hours but may introduce peak load demands of up to 0.75 MW. These findings highlight the importance of integrated energy modeling, smart charging strategies, and grid-aware planning